2009
DOI: 10.1051/0004-6361/200913030
|View full text |Cite
|
Sign up to set email alerts
|

Sunspot seismic halos generated by fast MHD wave refraction

Abstract: Aims. We suggest an explanation for the high-frequency power excess surrounding active regions known as seismic halos. Methods. We use numerical simulations of magneto-acoustic wave propagation in a magnetostatic sunspot model. Results. We propose that seismic halos can be caused by the additional energy injected by high-frequency fast mode waves refracted in the higher atmosphere due to the rapid increase of the Alfvén speed. Our model qualitatively explains the magnitude of the halo and allows us to make pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 27 publications
5
56
2
Order By: Relevance
“…that the fluid flows along field lines. Khomenko and Collados (2006) used the Pizzo (1986) sunspot model in numerical simulations of magnetoacoustic wave propagation, and more recently Khomenko and Collados (2008) produced a new set of models consisting of concatenation of self-similar models in the deep layers, where the gas pressure dominates over magnetic pressure, with models in which the pressure distribution is prescribed on the axis. In the deep photospheric layers, a self-similar solution for the magnetic field is calculated following the method of Low (1980), while the pressure and density distributions with height and radius are found from analytical expressions.…”
Section: Solution Of Full Mhs Force Balancementioning
confidence: 99%
See 2 more Smart Citations
“…that the fluid flows along field lines. Khomenko and Collados (2006) used the Pizzo (1986) sunspot model in numerical simulations of magnetoacoustic wave propagation, and more recently Khomenko and Collados (2008) produced a new set of models consisting of concatenation of self-similar models in the deep layers, where the gas pressure dominates over magnetic pressure, with models in which the pressure distribution is prescribed on the axis. In the deep photospheric layers, a self-similar solution for the magnetic field is calculated following the method of Low (1980), while the pressure and density distributions with height and radius are found from analytical expressions.…”
Section: Solution Of Full Mhs Force Balancementioning
confidence: 99%
“…The IAC MHD code, described by Khomenko and Collados (2006) and Khomenko, Collados, and Felipe (2008), solves the non-linear MHD equations for perturbations, written in the conservative form, using a fourth-order central difference scheme and advanced in time by a fourth-order Runge -Kutta method. In a similar manner to Stein and Nordlund (1998) and Caunt and Korpi (2001), in order to damp high-frequency numerical noise on subgrid scales, the physical diffusive terms in the equations of momentum and energy are replaced by artificial equivalents.…”
Section: The Iac Mhd Codementioning
confidence: 99%
See 1 more Smart Citation
“…This dependence is expressed in terms of the Abel integral equation (89), which can be solved analytically.…”
Section: General Helioseismic Inverse Problemmentioning
confidence: 99%
“…It is, generally, suggested that this enhancement is due to the interaction of acoustic waves with the canopy. There exist, in the literature, several mechanisms that try to explain the details of the nature of the observed enhancement (Carlsson & Bogdan 2006;Hanasoge et al 2009;Khomenko & Collados 2009;Kuridze et al 2008Kuridze et al , 2009Jacoutot et al 2009). …”
Section: Introductionmentioning
confidence: 99%